TIPOLOGI BADAN PERMUSYAWARATAN DESA RESPONSIF DALAM PEMBENTUKAN PERATURAN DESA YANG BERBASIS PARTISIPASI MASYARAKAT - Zaelani, Muhammad Aziz; Dewi, Nourma (Ilmu Hukum Prima (IHP), 2023)
The research reviews the problem of the Village Consultative Body accommodating community participation in forming Village Regulations and the ideal form of its typology that is responsive and based on community participation. The unresponsive Village Consultative Body impacts the making of Village Regulations that are non-participatory and executive-oriented. Village communities need more enthusiasm for participation. The research aims to create a standardized village community participation instrument aimed at the Village Consultative Body to create a responsive typology. The instrument becomes a reference for the Village Governing Body in accommodating village community participation in forming Village Regulations. This research is empirical with locations: (i) Kragilan Village, Mojolaban District, Sukoharjo Regency; (ii) Alastuwo Village, Kebakkramat District, Karanganyar Regency; (iii) Sojiwan Village, Ceper District, Klaten Regency; and (iv) Sawahan Village, Ngemplak District, Boyolali Regency. Data were obtained from Focus Group Discussions with qualitative analysis. The results of the research on the problems of the Village Consultative Body in accommodating community participation in the formation of Village Regulations include the need for more participation instruments, the low enthusiasm of the village community, and the less-than-optimal legislative aspects of the Village Consultative Body. The ideal form of a responsive Village Consultative Body typology in making Village Regulations based on community participation includes community participation through a partnership pattern between the Village Government and the Village community, establishing a Village Information Center, and optimizing the roles and functions of the Village Consultative Body.